Effectiveness of neuromuscular electrical stimulation for management of shoulder subluxation post-stroke: a systematic review with meta-analysis. (November 2017) - Lee, Jae-Hyoung; Baker, Lucinda L; Johnson, Robert E; Tilson, Julie K
Objectives: To examine the effectiveness of neuromuscular electrical stimulation (NMES) for the management of shoulder subluxation after stroke including assessment of short (1 hour or less) and long (more than one hour) daily treatment duration. Data sources: MEDLINE, CENTRAL, CINAHL, WOS, KoreaMed, RISS and reference lists from inception to January 2017 Review methods: We considered randomized controlled trials that reported neuromuscular electrical stimulation for the treatment of shoulder subluxation post-stroke. Two reviewers independently selected trials for inclusion, assessed trial quality, and extracted data. Results: Eleven studies were included (432 participants); seven studies were good quality, four were fair. There was a significant treatment effect of neuromuscular electrical stimulation for reduction of subluxation for persons with acute and subacute stroke (SMD:–1.11; 95% CI:–1.53, –0.68) with either short (SMD:–0.91; 95% CI:–1.43, –0.40) or long (SMD:–1.49; 95% CI:–2.31, –0.67) daily treatment duration. The effect for patients with chronic stroke was not significant (SMD:–1.25; 95% CI:–2.60, 0.11). There was no significant effect of neuromuscular electrical stimulation on arm function or shoulder pain. Conclusion: This meta-analysis suggests a beneficial effect of neuromuscular electrical stimulation, with either short or long daily treatment duration, for reducing shoulder subluxation in persons with acute and subacute stroke. No significant benefits were observed for persons with chronic stroke or for improving arm function or reducing shoulder pain.